Diversidade e valor de uso de plantas lenhosas na Baixada Maranhense, Amazonia Oriental, Brasil - AMORIM, Ingrid Fabiana Fonseca (2022)
Brazil has a great plant diversity that influences the social and economic field, due to the large collection of popular knowledge they have, influenced by the traditional communities that inhabit it and have direct access to nature and the applications of biodiversity. Tropical forests are of great importance for harboring an immense plant and animal diversity, which are sources of food and income for the traditional communities that inhabit them. The present study carried out an ethnobotanical survey in the Quilombola community of Pericumã located in the Baixada Maranhense, with the objective of knowing the use value (VU) and Relative Importance (RI) of the local flora and the conversational status of the species. The study was carried out in the quilombola community of Pericumã, municipality of Bequimão, where descriptions, citations of examined material, popular names, ethnobotanical descriptions were presented, relating to the potential use of the species. The research was explained to the participants, who were invited to sign the Free and Informed Consent Term, which was submitted and approved by the Research Ethics Committee of the Federal University of Maranhão- CEP-HUUFMA, (process no 4,612,680) and submitted to the Secretary of State for the Environment and Natural Resources (SEMA), with process no 2003260020. Thirty-two sense-type interviews were carried out in the 42 existing residences in the community of Pericumã, with heads of families, 12 of which were men aged 35 to 90 years old and 20 women 30 to 93 years old, the research took place between September 2019 and February 2020. The interviews were carried out individually at different times, as suggested by Phillips and Gentry (1993), seeking to avoid interference from third parties. In the ethnobotanical analyses, species use value (VU), rarefaction curve and Chao1 were used in order to demonstrate the sample sufficiency of the research and quantitative analyzes were carried out to verify the relative importance (RI) and use value (VU) of the species medicinal. A total of 136 vernacular plant names were cited, distributed in 109 genera and 46 families. A survey was carried out regarding the conservation status of plants according to the red list of threatened species, IUCN and CNCF, where we observed that some species are in the threatened category due to timber use in the region. It was still possible through semi-structured interviews to make a brief account of the history of the community, culture and way of life of the residents, which is extremely important for the community. The most representative families in the study were: Fabaceae with 16 species, Lamiaceae (11spp), Arecaceae (9 spp), Anacardiaceae (7spp), Rutaceae (6spp), Myrtaceae and Rosaceae (5 spp, respectively), Rubiaceae, Sapotaceae and Annonaceae with 4 spp each. The most cited forms of use were: Food, Medicinal, Construction and Technological, where the species that presented the highest VU were Babaçu (Attalea speciosa Mart. Ex Spreng.) (VU = 3.68), Manga (Mangifera indica L.) (VU = 1.34), Cashew (Anacardium occidentale L) (VU = 1.34). The plants of medicinal use had 77 vernacular names, distributed in 69 genera and 36 families. The highest Value in Use (VU) and Relative Importance (RI) was presented by the species Babaçu (Attalea speciosa Mart. ex Spreng.) (VU=3.68; RI= 2), being the most versatile species, followed by Cashew (Anacardium occidentale L) (VU= 1.34; RI=1), and the matruz (Dysphania ambrosioides (L.) Mosyakin & Clemants), which presented low VU, however it was the second species with the highest relative importance (RI=1.5). Regarding the conservation status, species were found in different threat categories such as: Vulnerable (VU), Least Concern (LC) and Near Threatened (NT), demonstrating the importance of ethnobotanical and ecological studies in the region. The species presented high Use Value (VU) and relative importance (RI) due to their socioeconomic and cultural importance in the Baixada Maranhense. The community of Pericumã demonstrated a vast knowledge about the local vegetation and its forms of use, demonstrating the need for more studies in the community aimed at the conservation of local species, due to the great floristic and cultural wealth. The community demonstrated a vast knowledge about medicinal plants and their various uses, as it is the first ethnobotanical record in the community, it is necessary to carry out more studies because the area has a great floristic and cultural wealth. It was possible to previously observe through the use categories mentioned by the interviewees that the extraction and use of plants for different purposes is still something very strong in the quilombo.